2013
DOI: 10.1155/2013/612459
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine Augmentation of Serotonin Reuptake Inhibitors in Severe and Long-Term Treatment-Resistant Obsessive-Compulsive Disorder

Abstract: The treatment recommendations in obsessive-compulsive disorder (OCD) after lack of response to selective serotonin reuptake inhibitors (SSRIs) include augmentation with other drugs, particularly clomipramine, a more potent serotonin reuptake inhibitor (SRI), or antipsychotics. We present two cases of response to lamotrigine augmentation in treatment-refractory OCD; each received multiple SRI trials over a >10-year period. The first patient had eleven years of treatment with multiple combinations including clom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…[16][17][18][19][20] In addition, in at least 1 previous case series, it was reported that some patients with hoarding disorder responded to extended-release methylphenidate. 21 Thus, our report suggests that the treatment of bipolar depression, when present, may help patients with different types of obsessivecompulsive and related disorder symptoms, including hoarding.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] In addition, in at least 1 previous case series, it was reported that some patients with hoarding disorder responded to extended-release methylphenidate. 21 Thus, our report suggests that the treatment of bipolar depression, when present, may help patients with different types of obsessivecompulsive and related disorder symptoms, including hoarding.…”
Section: Discussionmentioning
confidence: 99%
“…Arrojo-Romero et al 25 reported on successful LAM augmentation of SSRIs in 2 severe and long-term treatment-resistant OCDs.…”
Section: Lam In Obsessive-compulsive Disordermentioning
confidence: 99%
“…La lamotrigina ha mostrado eficacia al agregarse a un ISRS en pacientes resistentes de acuerdo a dos EADCCP (36,37), a un trabajo retrospectivo (38) y a reportes de casos (39,40). Asimismo, la adición de pregabalina es útil en pacientes con TOC resistente a la combinación de ISRS y antipsicóticos atípicos de acuerdo a un estudio abierto (41).…”
Section: Anticonvulsivantes / Estabilizadoresunclassified